2011
DOI: 10.1007/s00415-011-5998-9
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin treatment in neurological practice: how much does it really cost? A prospective cost-effectiveness study

Abstract: Botulinum toxin (BTA) is a safe and effective therapeutic tool for many neurological conditions but few studies have investigated its real cost in neurological practice. We evaluated the daily cost of botulinum toxin type A (BTA) treatment through a cost effectiveness analysis alongside a prospective study of BTA injections at a French University Hospital over a 2-year follow-up period. The data of 3,108 BTA injections performed in 870 adult patients presenting with dystonia, facial hemispasm, or spasticity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Yearly costs of botulinum toxin treatment for FD ranged from EUR 347 to EUR 3,633, depending on number of treatment sessions per year and type of dystonia treated [4, 5, 7, 10, 13]. The lowest costs were for treating BPS patients three times a year and the highest for treating CD patients five times a year [5, 10].…”
Section: What Are the Costs Of Btx Treatment?mentioning
confidence: 99%
See 2 more Smart Citations
“…Yearly costs of botulinum toxin treatment for FD ranged from EUR 347 to EUR 3,633, depending on number of treatment sessions per year and type of dystonia treated [4, 5, 7, 10, 13]. The lowest costs were for treating BPS patients three times a year and the highest for treating CD patients five times a year [5, 10].…”
Section: What Are the Costs Of Btx Treatment?mentioning
confidence: 99%
“…The lowest costs were for treating BPS patients three times a year and the highest for treating CD patients five times a year [5, 10]. Yearly costs for not treating FD patients were estimated to be between EUR 248 and EUR 1,014 and consisted of visits to the outpatient clinic, other medication and physiotherapy, among others [4, 13].…”
Section: What Are the Costs Of Btx Treatment?mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of CD’s effect on productivity has been recognized previously, although studies have not generally quantified it suitably for subsequent use in economic evaluations. For instance, a study of almost 300 patients by the Finnish Dystonia Association32 found 97 subjects (39%) had retired because of CD at a median age of 48 years, while many others reported sick leave, reduced productivity, and loss of employment 14,33. Similarly, a second study found 53.3% of patients with CD reported that employment status was negatively affected through reduced hours or responsibilities, including 18.9% of patients who had lost employment due to CD symptoms 15…”
Section: Discussionmentioning
confidence: 99%
“…In France, the annual cost of treating CD for patients who required BoNT-A injections in a neurological practice was estimated at, on average, €1,198 (2010), which included pharmaceutical costs of the BoNT-A injections and other medications, salaries, and conditioning and injection equipment. Differences in costs across patients were explained by the frequency of BoNT-A administration and duration of effect 22. However, at the present time, there are no other European studies that have estimated the overall economic burden of CD, including the UK.…”
Section: Introductionmentioning
confidence: 93%